On the intrinsic shape of oceanic eddies derived from satellite altimetry - Chen, Ge; Han, Guiyan; Yang, Xueqing (Remote sensing of environment, 2019)
The fundamental issue of mean eddy shape at the sea surface has been simplified as axially symmetric for a long time. This assumption is worth of a reexamination following significant advances in precise tracking of individual eddies, thanks to the recent availability of merged altimeter data with a grid resolution of 1/4° × 1/4° and a time interval of one day. Based on an orientationally aligned average of the effective boundaries of nearly 2.6 million individual eddies available to date, a characteristic shape of a “standard” eddy has been derived, which is found to be a very good approximation to a mathematical ellipsoid with a semimajor axis of a = 87.0 km, and a semiminor axis of b = 54.0 km. The oval nature of oceanic eddies appears to be universal in a climatological sense, but the best-fit ellipse varies with space and time. Statistically, the eddy ellipse has two preferred angles for its major axis: a primary angle of 104°/284° (nearly north-south) and a secondary angle of 171°/351° (nearly east-west). The intrinsic geometric asymmetry in eddy shape and orientation is believed to be one of the fundamental reasons behind the previously observed geophysical anisotropy in eddy properties. Future integrated analysis in an eddy-centric coordinate system with an ellipse geometry may open a new window into nonlinear mesoscale oceanography in terms of eddy kinetics and eddy dynamics. •The common eddy shape has been oversimplified as axially symmetric for a long time.•A characteristic shape of oceanic eddies has been derived as a well-defined ellipse.•The intrinsic oval shape leads to geophysical anisotropy in eddy properties.